Penerapan Mobile Crowdsourching Untuk Estimasi Waktu Kedatangan Bis Berdasarkan Informasi Masyarakat - Fauziah, Yuli; Rustamaji, Heru Cahya; Ramadhan, Rihadina Pambudi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2016)
Trans Jogja is a mass transportation system operating in Yogyakarta City, where the system has problems with the timeliness of departure and bus arrival, so the bus arrival schedule can not be ascertained. So, this study designs the application of mobile crowdsourcing concept to assist Trans Jogja bus users in terms of bus arrival estimation. The user broadcasts the location or when the passenger goes up so that the end-user passengers can get an estimate of how long the bus will come. The method used is qualitative method by collecting primary data source (interview, observation and literature study). This research involves passengers of Trans Jogja bus android smartphone users. Passengers post the status using the app to send the bus location. Other passengers who have been waiting at the bus stop can know the bus arrival time at the bus stop. Based on Performance test result, it can be obtained the average difference of bus arrival time in application with bus arrival time of survey result in line 1A is 1.86 minutes.
Keywords: Crowdsourcing; Trans Jogja; Waktu kedatangan bus.